2019
DOI: 10.21273/hortsci13903-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Quality on Vegetative Cutting and In Vitro Propagation of Coleus (Plectranthus scutellarioides)

Abstract: Coleus (Plectranthus scutellarioides) is an attractive and popular ornamental plant with propagation mainly achieved through vegetative cuttings. For commercial purposes, it is of interest to enhance the speed of establishment while maintaining high quality. Light quality has been shown to influence adventitious root development, so these experiments examined the effect of narrow-bandwidth light treatments on root growth and overall plant quality for seven coleus cultivars with vegetative cuttings in potting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…Chen et al (2019) reported that root generation and overall plant development can be dramatically promoted under available light intensity conditions in Haworthia [41]. At the same time, light quality is shown to influence ARs in Coleus [42]. We found that different light intensities have various roles in the formation of ARs in lotus.…”
Section: Discussionsupporting
confidence: 48%
“…Chen et al (2019) reported that root generation and overall plant development can be dramatically promoted under available light intensity conditions in Haworthia [41]. At the same time, light quality is shown to influence ARs in Coleus [42]. We found that different light intensities have various roles in the formation of ARs in lotus.…”
Section: Discussionsupporting
confidence: 48%
“…In the 'Favorita' potato (Solanum tuberosum L.) plantlets cultured in vitro, plant height was the greatest under monochromatic red light, whereas root length and fresh weight were the greatest under R/B (8/2), and chlorophyll content was the greatest under R/B (7/3) [11]. Cho et al [12] pointed out that the combination of red and green light (R/G, 80/20) increased more than twice as much roots and dry mass compared with W in Coleus (Plectranthus scutellarioides) in vitro culture, and the exposure to the combination of red, green and blue light (R/G/B, 40/20/40) significantly increased the chlorophyll content. LED can influence the physiological process of plantlets cultured in vitro through the optimal combination of different light qualities, so as to promote the growth and improve the quality of plantlets.…”
Section: Introductionmentioning
confidence: 99%
“…report that root generation and development can be dramatically promoted under available light intensity condition in Haworthia [42]. At the same time, light quality is shown to influence ARs in number [43]. We found that different light intensity showed various roles on ARs formation in lotus.…”
Section: Discussionmentioning
confidence: 60%